Antifungal activity and phytochemical analysis of selected fruit peels - Oladele Oluwole Olakunle; Joy Blessing Deborah; Okosodo Juliana Irene (Journal of Biology and Medicine - Peertechz Publications, 2019)
Antifungal activity and phytochemical analysis of selected fruit peels were investigated in this work. The selected peels, obtained from orange, pineapple cashew and banana fruits were air dried at 28±20C for four weeks and later grounded into powders. Extracts were prepared from each powder using water and ethanol as solvents. The antimicrobial activity of each of the aqueous extracts (100mg/ml) against Aspergillus niger and Alternaria alternata (test isolates) was assayed using agar well diffusion method.